1989
DOI: 10.1111/j.1439-0485.1989.tb00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Spatial Microdistributions of Foraminifers in an Intertidal Pool (Northern Adriatic Sea)

Abstract: Abstract. The spatial microdistribution of foraminifers was tested by the method of quadratic samplings on 2 sample grids in an intertidal pool of the northernmost Adriatic sea. Abundant species of foraminifers exhibit patchy distributions throughout; the distribution‐patterns of some species correspond nearly completely. Using statistical methods (regression‐ and correlation‐analyses) correlations to abiotic and biotic factors (water depth, exposure rate, seagrass, benthonic algae) were ascertained. The sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…This pattern suggests that C. teretis may reproduce most vigorously in localized areas where food (probably bacteria) is concentrated. Correlations between the small-scale distr~butions of benthic foraminifers and their probable food (cyanobacteria and diatoms) have been establish.ed in the intertidal North Adnatic (Hohenegger et al 1989) Sediment-dwelling species whlch are abundant in the July samples, for example Cassidulina teretis, 'Psammosphaera' sp, nov, and Trifarina pauperata, probably live on or wlthin the soft, flocculent surface sediment immediately beneath the detrital layer. One of these species, T, pauperata, is closely allied taxonomically and morphologically to the genus Uvigerina.…”
Section: Phytodetritus Populationsmentioning
confidence: 92%
See 1 more Smart Citation
“…This pattern suggests that C. teretis may reproduce most vigorously in localized areas where food (probably bacteria) is concentrated. Correlations between the small-scale distr~butions of benthic foraminifers and their probable food (cyanobacteria and diatoms) have been establish.ed in the intertidal North Adnatic (Hohenegger et al 1989) Sediment-dwelling species whlch are abundant in the July samples, for example Cassidulina teretis, 'Psammosphaera' sp, nov, and Trifarina pauperata, probably live on or wlthin the soft, flocculent surface sediment immediately beneath the detrital layer. One of these species, T, pauperata, is closely allied taxonomically and morphologically to the genus Uvigerina.…”
Section: Phytodetritus Populationsmentioning
confidence: 92%
“…There were also some significant differences in the abundance and variance of species in the total populations (Tables 7 to 9). Patchy distributions of benthic foraminiferal populations are well documented in both shallow water (Buzas 1968, 1970, Lee et al 1969, Matera & Lee 1972, Bernhard 1987, Hohenegger et al 1989) and the deep-sea (Bernstein et al 1978, Bernstein & Meador 1979, Kaminski 1985. Such spatial heterogeneity may have contributed to at least some of the differences observed between the April and July assemblages.…”
Section: Phytodetritus Populationsmentioning
confidence: 97%
“…The latter assumption corresponds to the preference of a diatom diet over sewage-derived POM (Ward et al, 2003), the presence of a diatom cracking mechanism (Austin et al, 2005), the sequestration of chloroplasts derived exclusively from diatoms (Knight and Mantoura, 1985;Pillet et al, 2011;Cevasco et al, 2015) or the correlation of the distribution of H. germanica populations with a high abundance of Nitzschia sp. (Hohenegger et al, 1989). This coherence with food availability or organic matter accumulation respectively, was used to explain population distributions of a H. germanica/A.…”
Section: Species-specific Food Uptakementioning
confidence: 99%
“…Elphidium gunteri is generally recorded in intertidal environments of the northern Adriatic Sea, which Hohenegger et al (1989) related to the high presence of blue-green algae -food dependency. It is common in the Goro (Po river delta, Italy) and S. Gilla lagoons (Coccioni, 2000;Buosi et al, 2010), but has not been reported in the Venice Lagoon, where it might be recognized as E. granosum, an iposaline taxon characteristic of low salinity areas (Albani & Serandrei Barbero, 1990).…”
Section: Ammonia Tepida and Ammonia Parkinsonianamentioning
confidence: 99%